PENGARUH KEPEMIMPINAN TRANSAKSIONAL DAN TRANSFORMASIONAL PADA KOMITMEN AFEKTIF - , Rudik Sanjaya Sugiarto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study examines the effect of transactional and transformational leadership on affective commitment at SMK 1 Mojokerto in East Java. Primary data collection, which is aimed to obtain answers on the research questions, is conducted through questionnaires. The sampling technique applied is census, 80 civil servant teachers were the respondents of this study. The data analysis testing applies a hierarchical regression analysis. The results, at the first stage of hierarchical regression analysis indicate that transactional leadership has significant positive effect on affective commitment. However, transactional leadership has no longer significant when controlling transformational leadership at the second stage of regression. At this stage also shows that transformational leadership has positive and significant effect on affective commitment. Further, transformational leadership provides additional explanation and significant variances on affective commitment more than they are explained by transactional leadership.